Corynebacterium pacaense sp. nov., Alistipes megaguti sp. nov., Alistipes provencensis sp. nov., 3 new bacteria isolated from fresh human stool specimens. (November 2019) - Bellali, S.; Naud, S.; Ndongo, S.; Lo, C.I.; Anani, H.; Raoult, D.; Lagier, J.-C.
Abstract: Here we describe the basic characteristics of Corynebacterium pacaense strain Marseille-P2417 T (= CSUR P2417), Alistipes megaguti strain Marseille-P5997 T (= CSUR P5997) and Alistipes provencensis strain Marseille-P2431 T (= CSUR P2431 = DSM 102308). The phenotypic criteria, the 16S ribosomal RNA sequencing and MALDI-TOF MS spectra analysis were used to identify and characterize these new bacteria species, which were isolated from fresh human stool specimens.